2014
DOI: 10.1080/10826076.2013.840842
|View full text |Cite
|
Sign up to set email alerts
|

HPLC-MS/MS Method for the Pharmacokinetics of Homosalate After Topical Administration in Rats

Abstract: & Homosalate is a UV filtering agent used in sunscreens and cosmetics for skin protection purposes. Despite the widespread use of these products, the extent of in vivo exposure to homosalate has not been elucidated. This study first reports the development of a rapid and sensitive high performance liquid chromatography-tanden mass spectrometry (HPLC-MS=MS) method for the analysis of homosalate in rat plasma and its pharmacokinetic characterization after topical application. Chromatographic separation was achie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…In particular, many studies have reported reduced ACC activity in people with schizophrenia (involving conventionally large effect size differences), which has been found when making errors or during high-conflict trials, including functional magnetic resonance imaging and electroencephalography studies. Moreover, there is evidence that impaired performance monitoring is associated with negative and disorganization symptoms [54] and predicts poor executive functioning in schizophrenia [55,56].…”
Section: Executive Functionmentioning
confidence: 99%
“…In particular, many studies have reported reduced ACC activity in people with schizophrenia (involving conventionally large effect size differences), which has been found when making errors or during high-conflict trials, including functional magnetic resonance imaging and electroencephalography studies. Moreover, there is evidence that impaired performance monitoring is associated with negative and disorganization symptoms [54] and predicts poor executive functioning in schizophrenia [55,56].…”
Section: Executive Functionmentioning
confidence: 99%